Decarboxylative [4+2] Cycloaddition by Synergistic Palladium and Organocatalysis. Issue 49 (7th November 2016) - Leth, Lars A.; Glaus, Florian; Meazza, Marta; Fu, Liang; Thøgersen, Mathias K.; Bitsch, Emma A.; Jørgensen, Karl Anker
Abstract: A novel reaction based on synergistic catalysis, combining palladium‐ and organocatalysis has been developed. The palladium catalyst activates vinyl benzoxazinanones via a decarboxylation to undergo a [4+2] cycloaddition with iminium‐ion activated α, β‐unsaturated aldehydes. The reaction is demonstrated to proceed for a number of combinations of vinyl benzoxazinanones reacting with α, β‐unsaturated aldehydes, providing highly substituted vinyl tetrahydroquinolines in good to high yields, and excellent enantio‐ and diastereoselectivities (>98 % ee and >20:1 d.r.). The palladium catalyst used in the synergistic catalysis can be re‐used in a one‐pot sequential coupling reaction with an aromatic boronic acid forming the coupling product in 95 % yield, >20:1 d.r. and 99 % ee . Abstract : The best of two worlds : A synergistic catalytic transformation combining palladium‐ and organocatalysis has been developed. The palladium catalyst activates vinyl benzoxazinanones via a decarboxylation to undergo a [4+2] cycloaddition with iminium‐ion activated α, β‐unsaturated aldehydes (see scheme).